On-farm management of agricultural biodiversity in Vietnam: Proceedings of a symposium, 6-12 December 2001, Hanoi, Vietnam - Tuan, H.D.; Hue, N.N.; Sthapit, B.R.; Jarvis, Devra I.; International Plant Genetic Resources Institute (2003)
Vietnam represents a country of ancient human culture, where agriculture has existed for millennia. It is the long history of agriculture and diverse ecological systems that grant Vietnam such an enormous diversity of plant genetic resources (PGR). Recently, the national and international concern about biodiversity conservation has risen as we become aware of its important role in the survival of humankind, particularly under conditions of climate change and environmental degradation. Consequently, the Government of Vietnam has made great efforts to facilitate PGR conservation and use. The first steps have resulted in successful conservation of biodiversity ex situ, which is known as the safest method. At present, however, the important role of in situ conservation in allowing evolution and adaptation processes, which are fully stopped by ex situ conservation, to take place, has gained more and more recognition. The project for ”Strengthening the Scientific Basis for in situ Conservation of agrobiodiversity on-farm” serves as a good expression of this common trend. Nine countries, namely Burkina Faso, Hungary, Mexico, Morocco, Nepal, Peru, Turkey, Vietnam and Ethiopia participate in this project. The main purpose is to develop essential knowledge to answer the questions WHAT, WHERE, WHEN and HOW in situ conservation can be effective. These proceedings contain the results achieved by Vietnamese partners in the first phase presented in the Project Annual Meeting organized by VASI and IPGRI-APO in Hanoi, Vietnam from 6 to 8 December 2001.